EXPERIMENTAL STUDY ON THE HEAT TRANSFER CHARACTERISTICS OF HYBRID NANOFLUID USING GRAPHENE NANOPLATELETS AND SILICON CARBIDE IN THERMAL OIL - CHAWFA, FAZEDEKA (2021)
Hybrid nanofluids are replacing unitary nanofluids in the heat transfer field. The combinations of different types of hybrid nanoparticles into a base fluid have led to the formation hybrid nanofluids with superior heat transfer performance, due to more controlled stability and thermophysical properties especially thermal conductivity, dynamic viscosity, and specific heat capacity.